The SAGE handbook of leadership - Bryman, Alan. (London : SAGE, 2011)
Leadership pervades every aspect of organizational and social life, and its study has never been more diverse, nor more fertile. With contributions from those who have defined that territory, this volume is not only a key point of reference for researchers, students and practitioners, but also an agenda-setting prospective and retrospective look at the state of leadership in the twenty-first century. It evaluates the domain and stretches it further by considering leadership scholarship from every angle, concluding with an optimistic look at the future of leaders, followers and their place in organizations and society at large.
Includes bibliographic references and indexes.
Keywords: Leadership -- Handbooks, manuals, etc